1998
DOI: 10.1074/jbc.273.33.21178
|View full text |Cite
|
Sign up to set email alerts
|

Complex NF-κB Interactions at the Distal Tumor Necrosis Factor Promoter Region in Human Monocytes

Abstract: We describe a dense cluster of DNA-protein interactions located 600 nucleotides upstream of the transcriptional start site of the human tumor necrosis factor (TNF) gene. This area was identified as being of potential importance for lipopolysaccharide-inducible TNF expression in the human monocyte cell line Mono Mac 6, based on reporter gene analysis of point mutations at a number of nuclear factor B (NF-B)-like motifs within the human TNF promoter region. The area contains two NF-B sites, which are here shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 29 publications
6
110
1
Order By: Relevance
“…As early as 20 min following stimulation with LPS, NF-B p65/p50 heterodimers bound to the B1 and B3 binding sites of the proximal TNF-␣ promoter, consistent with earlier studies (7,8). The current study extends these observations by directly documenting the functional relevance of these heterodimers, because expression of NF-B p65 and p50 resulted in greater than additive, or synergistic, activation of the TNF-␣ promoter.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As early as 20 min following stimulation with LPS, NF-B p65/p50 heterodimers bound to the B1 and B3 binding sites of the proximal TNF-␣ promoter, consistent with earlier studies (7,8). The current study extends these observations by directly documenting the functional relevance of these heterodimers, because expression of NF-B p65 and p50 resulted in greater than additive, or synergistic, activation of the TNF-␣ promoter.…”
Section: Discussionsupporting
confidence: 77%
“…We previously demonstrated that the Ϫ100/Ϫ74 oligonucleotide binds ectopically expressed C/EBP␤ (5,22) and it possesses the B3 binding site (8). Constitutively, there was minimal binding of NF-B to this oligonucleotide (Fig.…”
Section: Lps-induced Binding Of Nf-b and C-jun To The Tnf-␣ Promotermentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the factors that have been convincingly described as being involved in TNF transcription, including CREB, 157 C/EBPa þ b, [158][159][160] NFATp, [161][162][163] SP-1, Egr-1, 164 ATF2/JUN, 162,163,165,166 Nrf-1, 167,168 and Ets, 169 bind within the 200 bp proximal promoter. Although functional binding sites in the À600 region have been reported for NF-kB 170,171 and Litaf, 172,173 these regions harbour no known SNP. These considerations place a heavy burden of proof on data claiming to show functional activity outside of the 'core' promoter, or other regions for which there is independent evidence of protein binding.…”
Section: Functional Studies Of the Tnf Promotermentioning
confidence: 95%
“…35 The binding reaction and supershift experiments using antibodies raised against C/EBP b, Oct-1 and p65 NFkB (Santa Cruz Biotechnology, Santa Cruz, USA) were performed as described. 36 Statistics Data are summarized means with standard errors. The significance of differences in mean values, where the data had a normal distribution, was determined using a paired t-test.…”
Section: Il-8 Constructmentioning
confidence: 99%